ChemInform Abstract: [Sb7Se8Br2]3+ and [Sb13Se16Br2]5+ — Double and Quadruple Spiro Cubanes from Ionic Liquids. Issue 34 (26th August 2014) - Ahmed, Ejaz; Breternitz, Joachim; Groh, Matthias F.; Isaeva, Anna; Ruck, Michael
Abstract The new compounds obtained by reaction of Sb and Se in ionic liquids are characterized by single crystal XRD and DFT quantum chemical calculations.